Two‐Year Follow‐Up of the Efficacy of the PREP Training on Iranian Newlyweds. (24th July 2020) - Fallahchai, Reza; Fallahi, Maryam; Badiee, Manijeh
Abstract : The aim of the present study was to replicate the efficacy of the Prevention and Relationship Education Program (PREP) training on marital satisfaction and dyadic adjustment among a group of Iranian newlyweds. One hundred and sixty heterosexual couples ( N = 320 participants) were randomly assigned to an experimental or a wait list control group. Data from one hundred and forty‐eight couples were analyzed. Participants completed the ENRICH Marital Satisfaction Scale (The Family Journal, 1, 1993, 196–207) and Dyadic Adjustment Scale (The Journal of Sex Research, 39, 1976, 190–196) at pretest, posttest, 1‐year follow‐up, and 2‐year follow‐up. Results indicated that mean marital satisfaction and dyadic adjustment scores between the experimental and control groups were significantly different at posttest. Therefore, PREP training improved marital satisfaction and dyadic adjustment of couples at posttest. The data suggests that PREP training program can be introduced as an effective relationship education program for Iranian newlyweds.